Lessons from automatic airborne pollen monitoring by holography at three Australian sites - Andelija Milic; Beth Addison-Smith; Izhar Ullah; James K. Douch; Benedict J. Keaney; Paul J. Beggs; Simon G. Haberle; Janet M. Davies (Aerobiologia, 2026)
Automatic airborne pollen monitoring offers potential to enable real-time, sustainable environmental health information to assist with management of allergic respiratory disease. Automatic systems, however, have not been widely deployed in the Southern Hemisphere, where there is considerable biodiversity. An automatic holography-based device combined with a classification algorithm was trialled in Australia for 15 months over the main pollen seasons in subtropical Brisbane, and temperate Canberra and Sydney. Common airborne pollen taxa were monitored in parallel using Hirst-type volumetric traps, with manual observations serving as a reference. In Brisbane, the monitoring campaign coincided with the most extreme grass (Poaceae) pollen season ever observed. The automatic system assigned daily Poaceae pollen concentrations with high accuracy (ρ = 0.84, p p = 0.14). In Canberra, Poaceae and Betula were detected with a moderate to high correlation to manual observations (ρ = 0.67, p p Betula and Cupressaceae were, however, mistakenly assigned to Poaceae, and Betula was also misclassified as other Betulaceae taxa: Corylus and Carpinus . Pinaceae pollen was well recognized by the automatic system at this site (ρ = 0.59, p p = 0.35). The automatic system performed poorly in Sydney, where daily pollen concentrations were low, with high misassignment. While automatic pollen monitoring reduced the need for site visits and expedited daily forecasts, inconsistencies in classification and concentration levels between methods highlight the need to calibrate automatic systems to previously trained and locally relevant, regularly monitored pollen and their levels.

Functionalized benzylamines from commercial kraft lignin - Chang Dou; Minliang Yang; Nikhil Kumar; Rolin A. Aguilar; Addison J. Hitt; Griffen Gonzalez; Corinne D. Scown; Kenneth L. Sale; Hemant Choudhary; Aaron M. Socha; Ning Sun (Chemical Engineering Journal, 2026)

Toward an efficient framework for remote sensing of river bathymetry: Comparing sensors and algorithms on an inaccessible proglacial river in Alaska - Carl J. Legleiter; Christina M. Leonard; Paul A. Burger; Addison G. Pletcher; Paul J. Kinzel (Geomorphology, 2026)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Environmental DNA analysis of airborne poaceae (grass) pollen reveals taxonomic diversity across seasons and climate zones - Shanice Van Haeften; Bradley C. Campbell; Andelija Milic; Elizabeth Addison-Smith; Jane Al Kouba; Alfredo Huete; Paul J. Beggs; Janet M. Davies (Environmental Research, 2024)

Late Cenozoic environmental changes drove the diversification of a weevil genus endemic to the Cape Floristic Region - Noémie M.‐C. Hévin; Steffan Hansen; Pia Addison; Laure Benoit; Gael J. Kergoat; Julien Haran (Zoologica Scripta, 2022)
The Cape Floristic Region in the Republic of South Africa is a well‐recognized hotspot of biodiversity. Although this region is mostly known for its high level of plant diversity and endemicity, it also hosts an understudied and likely diverse arthropod fauna. Here we investigate the evolutionary history and timing of diversification of the apterous weevil genus Phlyctinus (Curculionidae: Entiminae), which is endemic to the coastal area and adjacent mountain ranges of the Cape floristic region and generally associated with sunflower plants (Asteraceae). We use a diverse array of molecular analyses (phylogenetic inference, molecular species delimitation and dating analyses) to analyse a novel molecular dataset of 202 weevil specimens (including 170 Phlyctinus sampled in 60 sites), and sequenced for two mitochondrial and four nuclear gene fragments. Phylogenetic and dating analyses indicate that the genus started diversifying in the late Miocene, with contrasting diversification dynamics for the three inferred clades, which present disjunct distributions. Host plant records and the lack of relatedness of species living in sympatry indicate that the diversification of Phlyctinus was predominantly driven by allopatric (geographic) speciation. We hypothesize that the interplay between topography and recurring cycles of coastline‐habitat fragmentation resulting from sea level oscillations spurred the diversification of the most speciose clade, whereas in the two remaining clades populations likely remained connected thus hampering allopatric speciation. Interestingly, this pattern echoes with the role of sea level oscillations as an important driver of the radiation of several lineages in the coastline ecosystems of the Cape Floristic Region.

Temporal Trends in Polybrominated Diphenylethers (PBDEs) in Blubber of Ringed Seals (Pusa hispida) from Ulukhaktok, NT, Canada Between 1981 and 2015 - R. F. Addison; D. C. G. Muir; M. G. Ikonomou; C. Dubetz; T. G. Smith; J. Alikamik (Archives of Environmental Contamination and Toxicology, 2020)

Quality control of pollen identification and quantification exercise for the AusPollen Aerobiology Collaboration Network: a pilot study - Andelija Milic; Beth Addison-Smith; Penelope J. Jones; Paul J. Beggs; Bircan Erbas; Janet M. Davies (Aerobiologia, 2020)

Calf muscle perfusion as measured with magnetic resonance imaging to assess peripheral arterial disease - Gerd Brunner; Jean Bismuth; Vijay Nambi; Christie M. Ballantyne; Addison A. Taylor; Alan B. Lumsden; Joel D. Morrisett; Dipan J. Shah (Medical & Biological Engineering & Computing, 2016)

Estrogen, progesterone, and HER2/neu receptor discordance between primary and metastatic breast tumours—a review - C. Yeung; J. Hilton; M. Clemons; S. Mazzarello; B. Hutton; F. Haggar; C. L. Addison; I. Kuchuk; X. Zhu; K. Gelmon; A. Arnaout (Cancer and Metastasis Reviews, 2016)

Investigating population differentiation in a major African agricultural pest: evidence from geometric morphometrics and connectivity suggests high invasion potential - M. Karsten; P. Addison; B. Jansen van Vuuren; J. S. Terblanche (Molecular Ecology, 2016)
The distribution, spatial pattern and population dynamics of a species can be influenced by differences in the environment across its range. Spatial variation in climatic conditions can cause local populations to undergo disruptive selection and ultimately result in local adaptation. However, local adaptation can be constrained by gene flow and may favour resident individuals over migrants—both are factors critical to the assessment of invasion potential. The Natal fruit fly ( Ceratitis rosa ) is a major agricultural pest in Africa with a history of island invasions, although its range is largely restricted to south east Africa. Across Africa, C. rosa is genetically structured into two clusters (R1 and R2), with these clusters occurring sympatrically in the north of South Africa. The spatial distribution of these genotypic clusters remains unexamined despite their importance for understanding the pest's invasion potential. Here, C. rosa , sampled from 22 South African locations, were genotyped at 11 polymorphic microsatellite loci and assessed morphologically using geometric morphometric wing shape analyses to investigate patterns of population structure and determine connectedness of pest‐occupied sites. Our results show little to no intraspecific (population) differentiation, high population connectivity, high effective population sizes and only one morphological type (R2) within South Africa. The absence of the R1 morphotype at sites where it was previously found may be a consequence of differences in thermal niches of the two morphotypes. Overall, our results suggest high invasion potential of this species, that area‐wide pest management should be undertaken on a country‐wide scale, and that border control is critical to preventing further invasions.

Stage-dependent differential expression of microRNAs in colorectal cancer: potential role as markers of metastatic disease - Michael M. Vickers; Jair Bar; Ivan Gorn-Hondermann; Nirit Yarom; Manijeh Daneshmand; Jennifer E. L. Hanson; Christina L. Addison; Timothy R. Asmis; Derek J. Jonker; Jean Maroun; Ian A. J. Lorimer; Glenwood D. Goss; et al. (Clinical & Experimental Metastasis, 2012)

Genetic structure of the southeastern United States loggerhead turtle nesting aggregation: evidence of additional structure within the peninsular Florida recovery unit - Brian M. Shamblin; Mark G. Dodd; Dean A. Bagley; Llewellyn M. Ehrhart; Anton D. Tucker; Chris Johnson; Raymond R. Carthy; Russell A. Scarpino; Erin McMichael; David S. Addison; Kristina L. Williams; Michael G. Frick; et al. (Marine Biology, 2011)

Analysis of population genetic structure of the green sea urchin ( Strongylocentrotus droebachiensis ) using microsatellites - J. A. Addison; M. W. Hart (Marine Biology, 2004)

An Integrated Approach to Street Canyon Pollution Modelling - Paul S. Addison; John I. Currie; David J. Low; Joanna M. McCann (Environmental Monitoring and Assessment, 2000)

CXC chemokines mechanism of action in regulating tumor angiogenesis - Bethany B. Moore; Douglas A. Arenberg; Christina L. Addison; Michael P. Keane; Peter J. Polverini; Robert M. Strieter (Angiogenesis, 1998)

Systematic mass rearing and release ofMicroctonus hyperodae (Hym.: Braconidae, Euphorinae), a parasitoid of the argentine stem weevilListronotus bonariensis (Col.: Curculionidae) and records of its establishment in New Zealand - S. L. Goldson; M. R. McNeill; J. R. Proffitt; G. M. Barker; P. J. Addison; B. I. P. Barratt; C. M. Ferguson (BioControl, 1993)

A new irregular coccus from the rumen of an oat-hay-fed jersey cow; effect on in vitro digestibility of corn stalks - Joan M. Macy; Rudolph B. Addison; J. Robert Farrand (Archives of Microbiology, 1984)